Localisation - When Language, Culture and Technology Join Forces - Byrne, Jody (Language at Work - Bridging Theory and Practice, 2009)
When you switch on your computer and type up a letter, what language do you see? What about when you visit a website or play a computer game? Does your mobile phone speak your language? Chances are that each of these technological marvels of the modern age communicates with you in your own language. For many of us, this is so commonplace and seamless that we hardly give it a moment’s thought but behind the scenes there is a whole industry dedicated to making sure that technology bridges the gap between language and culture without you even noticing.